Psychometric Study of the Raven Progressive Matrices Tests in elementary students from Lima - Delgado Vásquez, Ana (2002)
It was made a psychometric study of Raven Coloured Progressive Matrices Test, which is a non verbal instrument that evaluates abilities related to make comparisons, thinking for analogy and spatial perceptions organization. It was designed mainly as a measure of factor "g" of Spearman or general intelligence, composed by two abilities, named educational and reproductive. The participants were 2496 students obtained at random considering all school districts (USE) of the city of Lima, Peru. They were primary level students, from 1º to 6º grade and 6 to 11 years old. The psychometric analysis shows that the item-test relation is up to norms (>0.20), so reliability was attained. Also the factor analysis of the items comes up whith one factor explainig the 76% of variance, so construct validity was obtained. Also the calification norms was obtained. The analysis of results points out the comparison with other studies, the difference among students from public and private schools, and the difference that female and male students showed. Educational and social variables are used at formulating an explanation.